(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: The modified Bentall(M Bentall) procedure is considered as the gold standard for patients requiring aortic root replacement, where the native aortic valve is required to be replaced. Case Presentation: We hereby present a case report of a patient who was diagnosed having moderate to severe Aortic Regurgitation (AR) with aortic root aneurysm. He was treated successfully by us with the M.Bentall procedure. Conclusion: As the aortic disease detection and surgical expertise improved in our country, a M.Bentall procedure is a suitable and safe treatment option for Aortic root aneurysm. JCMCTA 2021 ; 32 (2) : 147-150